2023
DOI: 10.3390/rs15020299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Vegetation Change Based on Reconstructed Heterogenous NDVI in Seismic Regions

Abstract: The need to protect forests and enhance the capacity of mountain ecosystems is highlighted in the U.N.’s Sustainable Development Goal (SDG) 15. The worst-hit areas of the 2008 Wenchuan Earthquake in southwest China were mountainous regions with high biodiversity and the impacted area is typical of other montane regions, with the need for detecting vegetation changes following the impacts of catastrophes. While the widely used remotely sensed vegetation indicator NDVI is available from various satellite data so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…In this study, we found that in the Qipan catchment the NDVI immediately decreased sharply after the earthquake and gradually increased in the following years (Figures 6-8). This finding is consistent with the research results of Zhang et al [63], Shen et al [64], Wu et al [61], and others, indicating that coseismic landslides caused large areas of local vegetation to peel off, causing severe interference in the basin ecology, and these areas were prone to debris flows. Studies have confirmed that the decrease in landslide activity after an earthquake is related to the increase in vegetation restoration [65,66].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that in the Qipan catchment the NDVI immediately decreased sharply after the earthquake and gradually increased in the following years (Figures 6-8). This finding is consistent with the research results of Zhang et al [63], Shen et al [64], Wu et al [61], and others, indicating that coseismic landslides caused large areas of local vegetation to peel off, causing severe interference in the basin ecology, and these areas were prone to debris flows. Studies have confirmed that the decrease in landslide activity after an earthquake is related to the increase in vegetation restoration [65,66].…”
Section: Discussionsupporting
confidence: 92%
“…In short, in debris-flow-prone areas, it is meaningful to introduce vegetation evaluation into the variation in ecosystem stability. In this paper, we use the normalized difference vegetation index (NDVI), which is the most commonly used vegetation index and can better reveal the vegetation growth state and spatiotemporal changes in a basin, to evaluate vegetation [27,61]. Therefore, this study defines the ecosystem stability index based on the NDVI and IC, which is then used to comprehensively evaluate the ecological stability of debris-flow-prone areas after earthquakes.…”
Section: Assessment Of the Ecosystem Stability Of Debris-flow-prone A...mentioning
confidence: 99%